Scatter radiation reduction with a radiation-absorbing pad in interventional radiology examinations. Issue 132 (November 2020) - Koenig, A.M.; Maas, J.; Viniol, S.; Etzel, R.; Fiebich, M.; Thomas, R.P; Mahnken, A.H.
Highlights: Radiation absorbing pads significantly reduces the radiation dose, particularly for upper body parts. Additional radiation absorbing pad reduces the dose involved up to 80.6 % at eye level. At the height of 165 cm a lead equivalence of 0.5 mm showed a radiation dose reduction (51.4 %, p < 0.01) in comparison to a lead equivalence of 0.25 mm. Abstract: Purpose: Radiation-absorbing pads are an additional possibility to reduce scattered radiation at its source. The goal of this study is to investigate the efficacy of a new reusable radiation-absorbing pad at its origin in an experimental setup. Material and methods: All measurements were carried out using a clinical angiography system with a standardized fluoroscopy protocol, different C-arm angulations and an anthropomorphic torso phantom as a scattering body. An ionization chamber was used to measure the radiation exposure at five different heights of a simulated operator during a simulated transfemoral angiography intervention. Measurements were carried out with and without radiation-absorbing pads with lead equivalents of 0.25 and 0.5 mm placed onto the scattering body. For all measurements a mobile acrylic shield and an under-table lead curtain was used. Results: At all operator heights from 100 to 165 cm a significant radiation dose reduction of up to 80.6 % (p < 0.01) using the radiation-absorbing pad was measured, when compared to no radiation-absorbing pad. At the height of 165 cm the radiation-absorbing pad with a lead equivalence of 0.5 mm showed a significant radiation dose reduction (51.4 %, p < 0.01) in comparison to a lead equivalence of 0.25 mm. Conclusion: The addition of a radiation-absorbing pad to the standard protection means results in a significant dose reduction for the operator, particularly for upper body parts.